All Days 2015
DOI: 10.2118/178309-ms
|View full text |Cite
|
Sign up to set email alerts
|

Biological And Chemical Changes Associated With Exposure Of Cyprinid Fishes To Some Oil Field Chemicals In The Niger-Benue River System, Nigeria

Abstract: Oil and gas exploration and production in Nigeria is geared towards meeting the energy need of its populace and also generate revenue. However, oil field chemicals used in oil and gas activities are sources of environmental pollution, causing various degrees of harm especially to the aquatic components of the environment. Most ascertained detrimental effects of oil field chemicals on organisms are generally laboratory based investigations. These have not considered synergistic and antagonists effects of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The percentage concentration of 0.031% and 0.016% achieved 100% mortality within 4 hours of the test period. The corrosion inhibitor showed significant lethal effects on freshwater Tilapia guineensis, this collaborates previous research that corrosion inhibitors are toxic to fish and other aquatic organisms [21,22].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The percentage concentration of 0.031% and 0.016% achieved 100% mortality within 4 hours of the test period. The corrosion inhibitor showed significant lethal effects on freshwater Tilapia guineensis, this collaborates previous research that corrosion inhibitors are toxic to fish and other aquatic organisms [21,22].…”
Section: Resultssupporting
confidence: 89%
“…They further stated that among the production chemicals used for oil and gas production, corrosion inhibitor and biocide are the most toxic. Uche et al [17] in their work on the biological and chemical changes associated with the exposure of Cyprinid fishes to oilfield chemicals concluded that production chemicals have individual and synergetic toxic effects on the fish.…”
Section: Neff Et Al Stated That the Concentration Of Production Chemi...mentioning
confidence: 99%
“…River Nun is a bifurcation of the River Niger down in the Niger Delta. It has an aggregate length of 195 km with a mean width of 370 m. It flows via several communities in the state, through sparingly settled areas of freshwater, mangrove swamps and coastal sand ridges before completing its 160 km course to the Gulf of Guinea [16]. The river is used for several purposes comprising domestic, fishing and recreational, as well as ecological assets.…”
Section: Study Areamentioning
confidence: 99%
“…It has a total length of 195km and an average width of 370m, the Nun River is considered the largest river in Bayelsa State (Seiyahboh et al, 2013). It flows through several communities in Bayelsa State, through sparsely settled zones of freshwater and mangrove swamps and coastal sand ridges before completing its 160km course to the Gulf of Guinea (inlet of the Atlantic Ocean) (Uche et al, 2015). The river is used for domestic purposes, recreational, fishing and ecological assets.…”
Section: Description Of Study Areamentioning
confidence: 99%